Lewis basicity generated by localised charge imbalance in noble metal nanoparticle-embedded defective metal–organic frameworks - Ying Chuan Tan (Nature Portfolio, 2018)
Interactions between metal nanoparticles (NPs) and metal–organic frameworks (MOFs) in their composite forms have proven to exhibit beneficial properties. Here the authors present a unique approach to immobilise Pd NPs and, more importantly, to generate tunable basic sites within an anionic defective MOF.